Ultrahigh-strength and high-toughness steel member and preparation method thereof
By adopting low-cost cobalt-free martensite aging steel wire and arc additive manufacturing technology, combined with aging treatment and deep-cold treatment, the traditional ultra-high-strength martensite aging steel has been solved in terms of cost and toughness, and the rapid manufacturing and performance optimization of large ultra-high-strength steel components have been achieved.
Patent Information
- Application Number
- CN202411919348.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
AI Technical Summary
Traditional ultra-high strength martensite aging steel has shortcomings in terms of cost and toughness, and the heat treatment process consumes high energy and strict equipment requirements, making it difficult to achieve dual optimization of cost-effectiveness and material performance.
Low-cost cobalt-free martensite aging steel wire is used to quickly manufacture large ultra-high strength steel components through arc additive manufacturing technology, and heat treatment processes of aging and deep-cold treatment are adopted to optimize the microstructure and mechanical properties of the materials.
It achieves rapid manufacturing and cost reduction of large ultra-high strength steel components, while improving the comprehensive performance of the material, with high strength and good toughness, and is suitable for a wide range of application scenarios.
Smart Images

Figure CN119736560A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of additive manufacturing, and specifically relates to an ultra-high-strength and high-toughness steel component and a preparation method thereof. Background Art
[0002] Arc additive manufacturing technology is a wire-based directed energy deposition method that uses an arc as a heat source to melt the wire and deposit it layer by layer on a pre-planned additive path to form metal parts. This technology has the characteristics of large forming size, high deposition efficiency, low manufacturing cost, and short production cycle. It is the main manufacturing method for high-quality rapid prototyping of large metal components and is widely used in the rapid prototyping of large structural parts such as aerospace, pressure vessels, and armored vehicles.
[0003] Ultra-high strength maraging steel is used in aerospace and other fields because of its ultra-high strength and good impact resistance. However, traditional ultra-high strength maraging steel contains a large amount of expensive alloy elements, which leads to high cost and is difficult to achieve large-scale application. At the same time, the development of science and technology has put forward higher requirements on the performance of ultra-high strength steel. Maraging steel should have good toughness matching while having ultra-high strength.
[0004] The traditional heat treatment process of maraging steel usually includes solution treatment and subsequent aging treatment. The strengthening alloy elements in the steel are fully dissolved in the martensite through solution treatment, and the aging treatment is used to precipitate a variety of nano-scale dispersed intermetallic compounds on the ultra-low carbon martensitic matrix to achieve strengthening. Although this process can improve the strength of the material, it has shortcomings in toughness and cost-effectiveness. Solution treatment needs to be carried out at high temperature, with high energy consumption and strict requirements on equipment. In addition, although the aging treatment after solution treatment can promote the precipitation of intermetallic compounds, it has limited effect on improving toughness. Therefore, it is necessary to improve the heat treatment process to improve the comprehensive performance of ultra-high strength maraging steel and achieve dual optimization of cost-effectiveness and material performance. Summary of the invention
[0005] The purpose of the present invention is to provide an ultra-high strength and high toughness steel component and a preparation method thereof, based on low-cost cobalt-free maraging steel welding wire and adopting arc additive manufacturing technology to achieve rapid manufacturing of large ultra-high strength steel components.
[0006] The technical solution to achieve the purpose of the present invention is: a method for preparing an ultra-high strength and high toughness steel component, comprising the following steps:
[0007] Step (1): using cobalt-free maraging steel wire, the mass percentage of each element in the wire is as follows: C0-0.02%, Ti 0.5-0.6%, Al 0.1-0.2%, Ni 13.5-14.5%, Mo 2.5-3.5%, Cr 2.5-3.5%, Mn 0.5-1.5%, Si 0-0.02%, Fe balance;
[0008] Step (2): determining the process parameters and additive path of arc additive;
[0009] Step (3): component addition;
[0010] Step (4): Aging treatment: heating the component obtained in step (3) from room temperature to 450°C-480°C for 6±0.5 hours, then taking it out and air cooling it to room temperature;
[0011] Step (5): Cryogenic treatment: Place the component that has been air-cooled to room temperature in step (4) into a cryogenic medium, cool it to -190°C-130°C, keep it warm for 6-12 hours, and then take it out to obtain an ultra-high strength and high toughness steel component.
[0012] Furthermore, in step (1), the diameter of the wire is 1.0 mm to 1.6 mm.
[0013] Furthermore, the substrate used for additive manufacturing is a material such as low carbon steel, alloy steel, etc., which has a chemical composition similar to that of the wire.
[0014] Furthermore, the arc additive heat source is a plasma arc heat source, and the specific process parameters of the arc additive are: additive current 160±10A, wire feeding speed 1.05±0.05m / min, travel speed 1.2±0.05mm / s, swing amplitude 4±0.5mm, swing frequency 1Hz, and the ion gas and shielding gas used in the additive process are both 99.9% pure argon, the shielding gas flow rate is 20±1L / min, the ion gas flow rate is 1.2±0.1L / min, the single layer height of the deposited layer is 1.5±0.1mm, the width is 14±1mm, and the inter-pass offset is 7.5±0.5mm.
[0015] Furthermore, the additive path includes unidirectional additive within a layer and reciprocating additive between layers.
[0016] Furthermore, after each additive process in step (3) is completed, a temperature measuring device is used to detect the temperature of the arc extinction point of the process. After natural cooling to below 100°C, the welding gun is offset by 7.5±0.5mm and moved to the arc starting position of the next process for additive process. After a single layer of additive process is completed, the welding gun is lifted by 1.5±0.1mm and moved to the arc starting position of the next layer for additive process until the specified size of the component is reached.
[0017] Furthermore, the heating rate in step (4) is 10±1°C / min.
[0018] Furthermore, step (5) cryogenic treatment is as follows: placing the sample into a liquid nitrogen cryogenic device, cooling it to the target temperature, with a cooling rate of 5-15°C / min, and a total cooling time of less than 90min. After reaching the set temperature, keeping the temperature for 6-12h, then taking it out and heating it to room temperature.
[0019] An ultra-high-strength and high-toughness steel component is prepared by the above method.
[0020] The present invention adopts low-cost cobalt-free martensitic aging steel welding wire, and adopts intra-layer unidirectional additive and inter-layer reciprocating additive methods to perform additive by rationally planning the additive path. In-layer unidirectional additive is adopted, and the material deposition direction is consistent, which is helpful to form a uniform microstructure, reduce stress concentration and material unevenness caused by changes in deposition direction, and defects such as holes are not easy to occur at the overlap, and the forming quality is good; at the same time, inter-layer reciprocating additive is conducive to controlling the overall size of the component. When the arc is extinguished on one side, it is easy to collapse at the arc extinguishing point, while when the arc is extinguished on the inter-layer reciprocating additive, the arc extinguishing point is located on both sides of the component, and it is not easy to collapse significantly on both sides, which is conducive to the forming of the component. At the same time, in order to further strengthen the mechanical properties of the component, the component needs to be subjected to a certain heat treatment. The present invention adopts simple aging + cryogenic treatment, which can effectively improve the mechanical properties of the component. Aging treatment can cause many intermetallic compounds to precipitate on the matrix of the component, and the resulting strengthening effect can greatly improve the strength of the component. At the same time, part of the martensite is reversed to form reverse austenite during the aging process, so that the component still maintains good plasticity while improving the strength. At the same time, deep cryogenic treatment can effectively refine the grains, promote the transformation of austenite to martensite and make the martensite structure more stable and dense, thereby improving the strength and toughness of the material.
[0021] Compared with the prior art, the present invention has the following significant advantages:
[0022] The present invention adopts cobalt-free maraging steel welding wire, which significantly reduces the raw material cost in the component manufacturing process; at the same time, the arc additive manufacturing technology is used to manufacture, which can realize additive manufacturing of large and complex structural parts, with a shorter production cycle and lower manufacturing cost;
[0023] In view of the new low-cost ultra-high strength steel welding wire, the present invention proposes a heat treatment process scheme with simple process flow and low cost. The heat treatment process can effectively adjust the microstructure of the maraging steel material and optimize its mechanical properties, so that the prepared components ultimately have high strength and good toughness.
[0024] The invention can realize the preparation of ultra-high-strength and high-toughness components and has wide application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1It is a schematic diagram of the path planning of the additive component in the present invention.
[0026] Figure 2 It is a heat treatment process diagram of the present invention.
[0027] Figure 3 Schematic diagram of the plasma arc additive manufacturing system used in Example 1.
[0028] Figure 4 It is the macroscopic morphology of the component obtained by additive manufacturing in Example 1; wherein (a) is a top view of the additive manufacturing component, and (b) is a front view of the additive manufacturing component.
[0029] Figure 5 It is the microstructure morphology of the component before and after heat treatment in Example 1; wherein (a1) is the microstructure morphology of the additively treated sample at a magnification of 1000 times, and (a2) is the microstructure morphology of the additively treated sample at a magnification of 5000 times; (b1) is the microstructure morphology of the sample aged at 450℃ for 6h+-190℃ deep cooling for 6h at a magnification of 1000 times, (b2) is the microstructure morphology of the sample aged at 450℃ for 6h+-190℃ deep cooling for 6h at a magnification of 5000 times, (c1) is the microstructure morphology of the sample aged at 480℃ for 6h+-190℃ deep cooling for 6h at a magnification of 1000 times, and (c2) is the microstructure morphology of the sample aged at 480℃ for 6h+-190℃ deep cooling for 6h at a magnification of 5000 times.
[0030] Figure 6 It is a tensile curve diagram of the component after heat treatment in Example 1. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below in conjunction with the accompanying drawings.
[0032] A method for preparing an ultra-high-strength and high-toughness steel component comprises the following steps:
[0033] Step (1): using a cobalt-free maraging steel wire, wherein the mass percentage of each element is as follows: C 0-0.02%, Ti 0.5-0.6%, Al 0.1-0.2%, Ni 13.5-14.5%, Mo 2.5-3.5%, Cr 2.5-3.5%, Mn 0.5-1.5%, Si 0-0.02%, Fe balance;
[0034] Step (2): Determine the process parameters and additive path in the arc additive process: Determine the additive process parameters according to the wire in step (1), including but not limited to additive current, additive speed, wire feeding speed, and inter-path offset; select the additive path as intra-layer unidirectional additive and inter-layer reciprocating additive to ensure the forming quality of the additive component;
[0035] Step (3): Adding material to the component: Add material according to the additive process and additive path determined in step (2), and after each additive pass is completed, a temperature measuring device is used to detect the arc extinction point temperature of the pass. After naturally cooling to below 100°C, the welding gun is offset by the offset A between passes and moves to the arc starting position of the next pass to add material. After a single layer of additive material is completed, the welding gun is raised by one layer height and moved to the arc starting position of the next layer to add material until the specified size of the component is reached;
[0036] Step (4): Aging treatment: placing the component obtained by material addition in step (3) in a heat treatment furnace, heating from room temperature to 450°C-480°C for 6 hours, and then taking it out and air cooling it to room temperature;
[0037] Step (5): Cryogenic treatment: Place the component that has been air-cooled to room temperature in step (4) into a cryogenic treatment device, cool it to -190°C to -130°C, keep it warm for 6-12 hours, and then take it out to obtain an ultra-high strength and high toughness steel component.
[0038] In this application, the term "room temperature" refers to 25±5°C.
[0039] Example 1
[0040] The plasma arc additive manufacturing system is used to add material to the block component. The resulting component is 60mm high, 200mm long and 90mm wide. The plasma arc additive manufacturing system consists of Figure 3 As shown, the plasma arc system consists of a plasma welding power source (BHHF-500), an ESTUNER12-1510 six-axis industrial robot and its control cabinet (ESTUN ER12-K6B-PD), a wire feeding system and a water cooling system. The plasma welding gun is fixed at the end of the sixth axis of the robot.
[0041] The specific steps are as follows:
[0042] Step 1: Use low-cost cobalt-free maraging steel wire, the mass percentage of each element is as follows: C0-0.02%, Ti 0.5-0.6%, Al 0.1-0.2%, Ni 13.5-14.5%, Mo 2.5-3.5%, Cr 2.5-3.5%, Mn 0.5-1.5%, Si 0-0.02%, Fe balance, the wire diameter is 1.6 mm, and the substrate used for additive manufacturing is a 304 stainless steel substrate of 400 mm × 300 mm × 20 mm.
[0043] Step 2: Determine the process parameters and additive path in the additive process: Determine the additive process parameters based on the wire diameter test in step 1: additive current 160A, wire feeding speed 1.05m / min, travel speed 1.2mm / s, swing amplitude 4mm, swing frequency 1Hz, ion gas and shielding gas used in the additive process are both 99.9% pure argon, shielding gas flow rate is 20L / min, ion gas flow rate is 1.2L / min, the height of the single layer of the deposited layer is about 1.5mm, the width is about 14mm, and the offset between passes is 7.5mm. The additive path of the component is unidirectional additive within the layer and reciprocating additive between layers. The schematic diagram of the additive path is as follows Figure 1 shown.
[0044] Step 3: Component additive: Additive is performed according to the additive process and additive path determined in step 2, and after each additive process is completed, the temperature of the arc extinction point is detected by a temperature measuring device. After natural cooling to below 100°C, the welding gun is offset by 7.5mm and moved to the arc starting position of the next layer for additive. After a single layer of additive is completed, the welding gun is lifted by 1.5mm and moved to the arc starting position of the next layer for additive until the specified size of the component is reached. The macroscopic morphology of the component obtained by additive is as follows: Figure 4 shown.
[0045] Step 4: Aging treatment: Sample the components obtained by adding materials in step 3 and place them in a heat treatment furnace and heat them from room temperature to 450°C and 480°C, respectively. The heating rate is 10°C / min and the holding time is 360min. After aging, take them out and air cool them to room temperature.
[0046] Step 5: Cryogenic treatment: Place the components that have been air-cooled to room temperature in step 4 into cryogenic treatment equipment, cool down to -190°C, and the cooling rate is 5-15°C / min. The overall cooling time is less than 90 minutes. After reaching the set temperature, keep it warm for 360 minutes, then take it out and heat it to room temperature to obtain ultra-high strength and high toughness steel components.
[0047] Figure 5 The microstructure of the additive sample and the heat-treated sample in the middle area of the component. The middle area of the additive sample is mainly composed of lath martensite and austenite, and some precipitated phase particles can be observed on the surface of the matrix. The martensite content and the number of precipitated phases on the surface of the sample after heat treatment increased significantly, and the martensite and austenite grain sizes became finer. At the same time, compared with before heat treatment, the austenite distribution on the surface of the sample after heat treatment is more uniform, which is an important reason for the component to obtain ultra-high strength and high toughness. Figure 6 The figure shows the tensile curve of the sample after heat treatment. The tensile strength of the component can reach more than 1600MPa, and the elongation after fracture exceeds 15%, which has high strength and good toughness.
[0048] The present invention selects a new type of maraging steel material and performs arc additive manufacturing. The components obtained by additive manufacturing have a uniform structure after heat treatment and optimized mechanical properties. The prepared components ultimately have high strength and good toughness, and have good application value.
[0049] The present invention is based on low-cost cobalt-free martensitic aging steel welding wire and adopts arc additive manufacturing technology to achieve rapid manufacturing of large ultra-high strength steel components; at the same time, it provides a heat treatment process for the new cobalt-free martensitic aging steel, which includes aging treatment and cryogenic treatment, which not only simplifies the heat treatment process, reduces energy consumption and cost, but also can effectively improve the toughness of the material, achieving a perfect combination of ultra-high strength and high toughness. Through cryogenic treatment, the microstructure of the material is further optimized, the grains are refined, and the transformation from austenite to martensite is more complete, thereby significantly improving the comprehensive performance of the material.
Claims
1. A method for preparing an ultra-high strength and high toughness steel component, characterized in that: The steps include: Step (1): using cobalt-free maraging steel wire, the mass percentage of each element in the wire is as follows: C0-0.02%, Ti0.5-0.6%, Al 0.1-0.2%, Ni 13.5-14.5%, Mo 2.5-3.5%, Cr 2.5-3.5%, Mn 0.5-1.5%, Si 0-0.02%, Fe balance; Step (2): determining the process parameters and additive path of arc additive; Step (3): component addition; Step (4): Aging treatment: heating the component obtained in step (3) from room temperature to 450°C-480°C for 6±0.5 hours, then taking it out and air cooling it to room temperature; Step (5): Cryogenic treatment: Place the component that has been air-cooled to room temperature in step (4) into a cryogenic medium and cool it to -190°C to -130°C, then keep it warm for 6-12 hours and then take it out to obtain an ultra-high strength and high toughness steel component.
2. The method according to claim 1, characterized in that The diameter of the wire in step (1) is 1.0 mm to 1.6 mm.
3. The method according to claim 1, characterized in that: The component addition needs to be carried out on a substrate, and the substrate can be made of low-carbon steel, alloy steel and other materials with similar chemical composition to the wire.
4. The method according to claim 1, characterized in that: The arc additive heat source is a plasma arc heat source. The specific process parameters of arc additive are: additive current 160±10A, wire feeding speed 1.05±0.05m / min, travel speed 1.2±0.05mm / s, swing amplitude 4±0.5mm, swing frequency 1Hz, and the ion gas and shielding gas used in the additive process are both 99.9% pure argon. The shielding gas flow rate is 20±1L / min, the ion gas flow rate is 1.2±0.1L / min, the single layer height of the deposited layer is 1.5±0.1mm, the width is 14±1mm, and the inter-pass offset is 7.5±0.5mm.
5. The method according to claim 1, characterized in that: The additive paths include unidirectional additive within a layer and reciprocating additive between layers.
6. The method according to claim 1, characterized in that After each additive process in step (3) is completed, a temperature measuring device is used to detect the temperature of the arc extinction point of the process. After natural cooling to below 100°C, the welding gun is offset by 7.5±0.5mm and moved to the arc starting position of the next process for additive process. After a single layer of additive process is completed, the welding gun is raised by 1.5±0.1mm and moved to the arc starting position of the next layer for additive process until the specified size of the component is reached.
7. The method according to claim 1, characterized in that The heating rate in step (4) is 10±1°C / min.
8. The method according to claim 1, characterized in that Step (5) cryogenic treatment is as follows: placing the sample into a liquid nitrogen cryogenic device, cooling it to the target temperature, with a cooling rate of 5-15°C / min, and a total cooling time of less than 90min. After reaching the set temperature, keep it warm for 6-12h, then take it out and heat it to room temperature.
9. An ultra-high strength and high toughness steel component, characterized in that: The method is prepared by any one of claims 1 to 8.
Citation Information
Cited By
A high-strength maraging stainless steel with a multi-stage aging process and its preparation method and application
CN120230970B
Ultrahigh-strength steel for aviation component and preparation method for improving strength and plasticity
CN121911910A